2012
DOI: 10.1590/s1806-83242012000300012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Er,Cr:YSGG and Er:YAG laser irradiation on the adhesion of blood components on the root surface and on root morphology

Abstract: The aim of this study was to conduct an in vitro evaluation, by scanning electron microscopy (SEM), of the adhesion of blood components on root surfaces irradiated with Er,Cr:YSGG (2.78 µm) or Er:YAG (2.94 µm) laser, and of the irradiation effects on root surface morphology. Sixty samples of human teeth were previously scaled with manual instruments and divided into three groups of 20 samples each: G1 (control group) -no treatment; G2 -Er,Cr:YSGG laser irradiation; G3 -Er:YAG laser irradiation. After performin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
1
4
0
1
Order By: Relevance
“…(Figure 3) (Table 3) These findings are in accordance with a similar study,19 but contradict a study by Theodoro et. al.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…(Figure 3) (Table 3) These findings are in accordance with a similar study,19 but contradict a study by Theodoro et. al.…”
Section: Discussionsupporting
confidence: 85%
“…In some studies blood was applied on the conditioned root surfaces to mimic the periodontal surgery procedure and blood components attachment was observed. When different lasers were compared, root surfaces treated with ER:YAG laser presented a better adhesion of blood cell attachment and a better fibrin network formation 18, 19. In a separate study, evaluation of blood cell attachment on EDTA-treated root surfaces was not found successful 21.…”
Section: Introductionmentioning
confidence: 99%
“…From the point of view of the morphological aspect of the root surface treated with these lasers, in vitro studies have shown that both Er:YAG and Er,Cr;YSGG lasers promote changes in the surface making them more irregular and rough. 5,6,7,30,31,32 These changes in the surface result from the explosive ablation process typical of these lasers, maintaining biocompatible surfaces when used with parameters adequate irradiation. 6,31,33 These lasers are also indicated for removal of dental calculus, non-surgical treatment of periodontitis (bacterial reduction) and soft or mineralized tissue ablation procedures.…”
Section: Er:yag and Ercr:ysgg Lasersmentioning
confidence: 99%
“…5,6,7,30,31,32 These changes in the surface result from the explosive ablation process typical of these lasers, maintaining biocompatible surfaces when used with parameters adequate irradiation. 6,31,33 These lasers are also indicated for removal of dental calculus, non-surgical treatment of periodontitis (bacterial reduction) and soft or mineralized tissue ablation procedures. 2,3 In addition, it has been shown that the Er:YAG laser promotes a reduction in pulp temperature that may also be associated with exterior cooling.…”
Section: Er:yag and Ercr:ysgg Lasersmentioning
confidence: 99%
“…Son zamanlarda erbium katkılı itriyum alümin-yum garnet laser (Er:YAG) ile çok daha olumlu sonuçlar alınmıştır. Subgingival diştaşları ablete edilerek uzaklaştırılmakta, periopatojen bakteriler elimine edilmekte, hatta sement yüzeyindeki lipopolisakkarit yapısındaki endotoksinler de inaktive edilmektedir [22][23][24][25][26] . El aletleriyle ve laser ile yapılan SRP işlemleri karşılaştı-rıldığında; laserin kök yüzeyini daha fazla pürüzlen-dirdiği, geride hiç smear tabakası bırakılmadığı, kan komponentlerinin ve fibroblastların yüzeye adezyonunu kolaylaştırdığı ve böylece rejeneratif tedaviyi kolaylaştırdığı gösterilmiştir [24][25] .…”
Section: Ultrasonik Ve Sonik Aletlerle Yapılan Diş Taşı Temizliği Ve unclassified